Nove interpretacije fluvialnih sedimentov na Krasu - Mihevc, Andrej (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2007)
Important unroofed caves with fluvial sediments from Divaški kras, Matarsko podolje and Podgorski kras are presented. Extend of the phenomena and relation to the existing caves and karst surface and geomorphological meaning of them are described. Sediments from them were analysed and dated with different methods. The largest age of the sediment was found in the unroofed cave excavated in Črnotiče quarry. In the cave wall fossil remains of stygobiont Marifugia cavatica were covered by 3.2-4.1 Ma old fluvial sediments.
Keywords: fizična geografija; physical geography; geomorfologija; geomorphology; krasoslovje; kraške jame; List of caves in Slovenia; kraške vode; sedimenti; rečni sedimenti; Slovenia; Slovenija; karst; Kras